The Existence of Solution for a k-Dimensional System of Multiterm Fractional Integrodifferential Equations with Antiperiodic Boundary Value Problems - Dumitru Baleanu; Sayyedeh Zahra Nazemi; Shahram Rezapour (Abstract and Applied Analysis)
There are many published papers about fractional integrodifferential equations and system of fractional differential equations. The goal of this paper is to show that we can investigate more complicated ones by using an appropriate basic theory. In this way, we prove the existence and uniqueness of solution for a k-dimensional system of multiterm fractional integrodifferential equations with antiperiodic boundary conditions by applying some standard fixed point results. An illustrative example is also presented.